IMPLEMENTASI LEMBAR PENILAIAN POTENSI BAHAYA BERDASARKAN FRAMEWORK PENILAIAN POTENSI BAHAYA IDEACM DI INDUSTRI MENGGUNAKAN PENDEKATAN ERGONOMI MAKRO (STUDI KASUS: PT XYZ) - Dinda Okta Dwiyanti Ridwan Gucci; Yopy Mardiansyah (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
Hazard is something that can potentially cause harm. Losses can be in the form of health problems or injuries to humans (workers), loss of work time, damage to property, area or workplace, products or damage to the surrounding environment, losses in the production process or other damages. Therefore, need for a comprehensive assessment of potential hazards. The purpose of this hazard assessment is to find out how much potential hazards the work station has. In this problem requires a solution in order to calculate how much the overall potential hazard, so the solution is to use a potential assessment sheet with a macro ergonomics approach. In the final results of the hazard potential assessment sheet is given a ranking, in order to determine the largest to the smallest potential at the work station. It also provides a quick conclusion to determine the potential hazards of macro ergonomic elements that must be carried out in advance in order in the ranking.